(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
This article focuses on the cremation burial ritual in ancient Latium during the 3rd and 4th phase, dated from the end of the Iron Age to the beginning of the Orientalizing Period, coinciding with the merging of a stratified society. This ritual, already uncommon during the 2nd phase, becomes exceptional in the later phases. A detailed analysis of all cases in every single centre of Latium shows this particular feature of funerary practices to be seen as an evident consequence of direct contacts with the Greek world and not only with Etruria and the Fossakultur. In the present study its evaluation takes into account that such an innovation in ritual practices, received from abroad and filtered by local sensibility and tradition, is a sign of cultural enrichment and not of decadence.